Examining the relationship between creativity and cognitive flexibility in early childhood - Kan, Erica E Shan (Nanyang Technological University, 2023)
Extensive research has been dedicated to examining the relationship between creativity and executive functions. However, the contribution of cognitive flexibility to the various aspects of creativity, particularly in early childhood, remains understudied. This study thus seeks to bridge this information gap. Hypothesis: It was hypothesised that greater cognitive flexibility is most strongly associated with greater originality of ideas. Methods: 20 children ranging from 12 to 30 months were recruited. A recently developed creativity battery consisting of the modified Unusual Box Test (UBT), adapted Thinking Creatively in Action and Movement (TCAM) and Exploratory Play was utilised to obtain fluency, originality and explore ratios. In addition, the Object Categorisation and Sequential Touching Task (OCSTT) and A-not-B task were used to assess cognitive flexibility. Performance indices on the tasks were obtained using behavioural coding and live scoring. Results: Some positive associations were found between OCSTT performance and originality scores, as well as OCSTT performance with fluency scores. However, no significant relationship was found between cognitive flexibility and child exploratory behaviour. Comparisons of creativity sub-constructs with the A-not-B task yielded indeterminate results. Discussion: Results partially supported the hypothesis. This could be due to various limitations such as the small sample size and the subjective nature of behavioural coding. Future studies can make relevant adjustments to the present study to obtain more meaningful results.